2019
DOI: 10.1177/1129729819872881
|View full text |Cite
|
Sign up to set email alerts
|

An innovative cyanoacrylate device developed to improve the current standard of care for intravascular catheter securement

Abstract: Introduction: Over one billion intravascular devices are used worldwide, annually. Due to the associated complications with these devices, the development of a reliable yet cost-effective securement technique is extremely important. The purpose of this study is to demonstrate the strength of a novel catheter securement cyanoacrylate for securing peripheral venous catheters, central venous catheters, peripherally inserted central catheters, and all other intravascular catheter types. Materials and methods: An u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The CSCAs were tested to prove the securement capabilities over a week-long period. The securement strength for CSCAs for securing Insyte Autoguard and Nexiva catheters at 7 days after initial securement was 16.36 N and 15.72 N, respectively 35…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The CSCAs were tested to prove the securement capabilities over a week-long period. The securement strength for CSCAs for securing Insyte Autoguard and Nexiva catheters at 7 days after initial securement was 16.36 N and 15.72 N, respectively 35…”
Section: Discussionmentioning
confidence: 98%
“…The study confirmed that SecurePortIV provides an effective sealant layer for the insertion site and a sufficient moisture barrier against aqueous solutions. The effective seal of SecurePortIV on the catheter insertion site may help reduce dressing changes 35,40. The 2021 Infusion Therapy Standards of Practice (the Standards ), which includes the additional option of TA use for stabilizing and securing VADs, now provides a better alternative for a catheter securement device that offers a full seal around the insertion site 24…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations